Girls Violating the Law - Andrea Cristina Coelho Scisleski; Giovana Barbieri Galeano (Oñati Socio-Legal Series)
This article is the result of a research that problematizes the public policies directed to the youth that commits offensive conducts, especially the adolescent women. Guided by Michel Foucault's thought, we discuss and analyze how the discourse on the young population in conflict with the law is operationalized to legitimize interventions in the socio-educational environment. We started from the Foucauldian archaeogenealogy to think about the present in power-knowledge relations, reflecting on the discourses on the rights of young women who serve socio-educational measures, because the policies of socio-education have been designed for young men, invisibilizing the specific conditions that imply the entry of girls into the Brazilian justice system. The operationalization of public policies for youth in conflict with the law, in the present, indicates the implementation of measures that, subsidized by speeches produced in the relationship between health institutions and justice, violate the rights guaranteed by law.